ANALISIS SEMIOTIKA ROLAND BARTHES NASKAH DRAMA SANG MANDOR KARYA RAHMAN ARGE - Muthia Nur Rohmah; Joko Purwanto (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
The purpose of this study is to identify and analyze the moral values contained in the drama script Sang Mandor written by Rahman Arge. This research employs a descriptive qualitative method using a semiotic approach based on Roland Barthes’ semiotic theory. The focus of this research is on the five semiotic codes: hermeneutic, semic, symbolic, proairetic, and gnomic. The analysis reveals that the script fulfills all five of Roland Barthes' semiotic codes. These codes are conveyed through narration, conflict, and dialogue between the characters, making this drama rich in semiotic codes that can be thoroughly examined.